2011
DOI: 10.1007/jhep01(2011)061
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Parton Interactions in Z+ jets production at the LHC. A comparison of factorized and non-factorized double parton distribution functions.

Abstract: Abstract:We examine the contribution of Multiple Parton Interactions to Z + n-jets production at the LHC, n = 2, 3, 4, where the Z boson is assumed to decay leptonically. We compare the results obtained with the correlated GS09 double parton distribution function with those obtained with two instances of fully factorized single parton distribution functions: MSTW2008LO and CTEQ6L1. It appears quite feasible to measure the MPI contribution to Z+2/3/4 jets already in the first phase of the LHC with a total lumin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…The effects of such multiparton interactions are suppressed or average out in sufficiently inclusive observables, but they have important consequences for the details of the hadronic final state. The possible importance of multiparton interactions has been realized long ago [1,2] and phenomenological estimates have been given for many final states such as four jets (possibly including b quarks) [3][4][5][6][7][8][9], jets associated with photons or leptons [10], four leptons produced by the double Drell-Yan process [11][12][13] or from two charmonium states [14][15][16], as well as a number of channels with electroweak gauge bosons [17][18][19][20][21][22][23][24][25][26]. Experimental evidence for multiple hard scattering has been found in the production of multijets [27][28][29] and of a photon associated with three jets [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of such multiparton interactions are suppressed or average out in sufficiently inclusive observables, but they have important consequences for the details of the hadronic final state. The possible importance of multiparton interactions has been realized long ago [1,2] and phenomenological estimates have been given for many final states such as four jets (possibly including b quarks) [3][4][5][6][7][8][9], jets associated with photons or leptons [10], four leptons produced by the double Drell-Yan process [11][12][13] or from two charmonium states [14][15][16], as well as a number of channels with electroweak gauge bosons [17][18][19][20][21][22][23][24][25][26]. Experimental evidence for multiple hard scattering has been found in the production of multijets [27][28][29] and of a photon associated with three jets [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution to the cross section from the second term induced by the QCD evolution cannot be reduced to the form (5) with some new constant effective cross section as it was done in earlier estimations [35,40,41]. The QCD evolution effects for the cross section are anticipated to be larger than for the two-parton distribution functions, for those such effects were estimated in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…(1). We name it as "simply factorized" (SF) dPDF, which is widely used both in theoretical [39,[48][49][50][51][52][53][54][55][56][57] and experimental studies [4][5][6][7][8][9][10][11][12][13]24,36,37].…”
Section: Frameworkmentioning
confidence: 99%
“…The comparison of the SF and GS09 dPDFs has been investigated in the Z ⊗ jets channel [48] and the W ⊗ W channel [39]. It was shown that both the SF and GS09 dPDFs give rise to consistent cross sections within ∼10% accuracy and, furthermore, the kinematics distributions of p T , η and invariance mass are insensitive to the choice of dPDFs.…”
Section: Simple Factorized Dpdf Versus Gs09 Dpdfmentioning
confidence: 99%
See 1 more Smart Citation